PENINGKATAN KESEJAHTERAAN PETANI MELALUI STRATEGI PENGUATAN KELEMBAGAAN EKONOMI DI KABUPATEN KONAWE UTARA (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
The purpose this study was to identify; economic institutions of society, Institutional constraints and community economic development in North Konawe. The study was conducted on the economic institutions of society in North Konawe by taking samples at five districts. Data were collected by in-depth interviews and documentation. Data analysis was performed through the reduction, presentation and verification. The study concluded: 1.The Economic Institute of the communities in district North Konawe are cooperatives and farmer groups, 2.An obstacle to development of economic institutions of society, namely: a).Cooperatives: members do not understand the purpose of establishing a cooperative, members simply as a requirement for the establishment, the management does not understand the principle of cooperation and good business management, lack of supervision, the local government policies do not support. b). Farmers; Lack of transparency and credibility of the board, still considers aid as funds ran out, supervision is not maximized, access to financial institutions is difficult, the lack of funds and market information. Efforts to the development of economic institutions of society in North Konawe, namely; maximizing the role of government in capital/equipment and surveillance, training about the management, maximization supervision, the role of extension workers.